2016
DOI: 10.1002/maco.201508655
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen embrittlement of high strength steel under in situ corrosive charging conditions and tensile load

Abstract: It is known that advanced and ultra‐high strength steel grades (AHSS and UHSS) are susceptible to hydrogen embrittlement under certain test conditions . In this study, punched hole specimens for constant load testing with in situ hydrogen charging were used to quantify the effect of different corrosive conditions. Flowing or stagnant electrolyte (5% NaCl) conditions were established and time to failure was recorded as a function of applied tensile stress. The pH of the solution was set at 2, 7, and 12. Bare an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
3
5
0
Order By: Relevance
“…The here‐observed hydrogen‐induced expansion of ≈11% is by far too large to be accommodated by elastic deformation, whether in the bulk or thin film, and the swelling must be accompanied by plastic deformation . This is consistent with reported hydrogen‐induced embrittlement . Severe local structural disruption of the protective passive layer induced by swelling is also a plausible explanation for the reported hydrogen‐induced diminished resistance to pitting corrosion …”
Section: Resultssupporting
confidence: 86%
“…The here‐observed hydrogen‐induced expansion of ≈11% is by far too large to be accommodated by elastic deformation, whether in the bulk or thin film, and the swelling must be accompanied by plastic deformation . This is consistent with reported hydrogen‐induced embrittlement . Severe local structural disruption of the protective passive layer induced by swelling is also a plausible explanation for the reported hydrogen‐induced diminished resistance to pitting corrosion …”
Section: Resultssupporting
confidence: 86%
“…A greater hydrogen concentration thereby increased the hydrogen influence. This was consistent with the fact that Scharf et al [54] found that zincgalvanized high-strength steels possessed higher hydrogen concentrations, and consequently lower resistance to hydrogen induced delayed fracture when immersed in a NaCl solution.…”
Section: Qpsupporting
confidence: 88%
“…Based on the research of Scharf et al [50] a hydrogen content of approximately 1.2 wt. ppm is sufficient to cause embrittlement of a ferritic-martensitic high-strength dual-phase steel that is loaded at 80% of its YS.…”
Section: Introductionmentioning
confidence: 99%